Por uma igreja de rosto amazônico. Inculturação dos ministérios eclesiais - Tavares, Sinivaldo Silva (Revista Eclesiástica Brasileira, 2020)
Na Exortação pós-sinodal Querida Amazônia, o Papa Francisco apresenta o Documento final do sínodo “de maneira oficial” e, por esta razão, em vez de querer superá-lo ou substituí-lo, convida “a lê-lo integralmente”. Daí o fato de sugerir “uma recepção harmoniosa, criativa e frutuosa de todo o caminho sinodal” (QA, 2). Como articular o Documento final com a Exortação pós-sinodal com vistas a uma potencialização recíproca? Reputa-se que questões candentes emersas no curso do longo processo sinodal continuam postas sobre a mesa. E isso justificaria, portanto, o fato de se continuar refletindo sobre as mesmas. A teologia tem por missão iluminar a prática pastoral no intuito de torná-la mais lúcida e eficaz. Nesse sentido, serão aqui problematizadas algumas das questões em torno a três nós temáticos: 1) a Igreja faz a Eucaristia, mas é a Eucaristia que edifica a Igreja; 2) a ”privatização” do ministério ordenado e da eucaristia; 3) a relação entre “sacerdócio batismal” e “sacerdócio ministerial”. Antes, porém, são partilhadas algumas perplexidades relativas, sobretudo, às questões tratadas nos parágrafos que se situam no quarto capítulo, intitulado “Sonho eclesial”, e, mais precisamente, nos números relativos à “inculturação do ministério” (n. 85-90) e à “força e dom das mulheres” (n. 99-103). Manifesta-se, enfim, a convicção de que tais questões devam ser analisadas e aprofundadas no horizonte de uma eclesiologia de comunhão enredada ao redor do binômio comunidade-ministérios. Abstract: In the post-synodal Exhortation Dear Amazon Pope Francis presents the final document of the synod “in an official manner” and for this reason, instead of wanting to go beyond or replace it invites us to “read it in its entirety”. Hence his suggestion for “a harmonious, creative and fruitful reception of the entire synodal path” (QA, 2). How to link the final Document with the post-synodal Exhortation with the intention to produce a reciprocal enhancement? It is believed that complex topics kept under the surface throughout the long synodal process continue on the table. This would justify, therefore, the fact that we continue to reflect about them. Theology has as its mission to throw light on the pastoral practice in order to make it clearer and more effective. In this sense, some of the issues around three thematic knots there will be discussed and analyzed here: 1) the Church makes the Eucharist but it is the Eucharist that builds the Church; 2) the “privatization” of the ordained ministry and of the Eucharist; 3) the relation between “baptismal priesthood” and “ministerial priesthood”. Before this, however, some perplexities related, above all, to the issues dealt with in some paragraphs of the fourth chapter – entitled Ecclesial Dream – are shared. And, more precisely, the numbers related to the “enculturation of the ministry” (n.85-90) and to “the strength and gifts of women” (n. 99-103). Finally, the conviction that such issues must be further analysed and studied more deeply in the horizon of a communion ecclesiology entangled with the binomial community-ministries. Keywords: Eucharist; Inculturation; Baptized priesthood; Community; Ministries.